What are we aiming for?—A Delphi study on the development of civic scientific literacy in Sweden. Issue 2 (4th March 2017) - Chang Rundgren, Shu-Nu; Rundgren, Carl-Johan
ABSTRACT: Based on the EU FP 7 project, PROFILES, this article presents our findings from a three-round Delphi study conducted in Sweden that aimed at establishing a consensus on how science education should be developed for citizens to enhance civic scientific literacy. A total of 100 stakeholders (9th graders, school teachers, scientists, and science education researchers) were involved in our Delphi study in 2012–2013. The results revealed that there were some highly ranked consensus ideas: environmental issues, inquiry skills, motivation/interest, and holistic comprehension. The conclusions of our research imply the importance of involving different stakeholders in the educational reconstruction process; we suggest that schoolteachers in particular should play a vital role.